The REtirement in ACTion exercise programme and its effects on elements of long term functionality in older adults - Ladlow, Peter; Western, Max J.; Greaves, Colin J.; Thompson, Janice L.; Withall, Janet; Koning, Jolanthe de; Bollen, Jessica C.; Moorlock, Sarah J.; Guralnik, Jack M.; Fox, Kenneth R.; Stathi, Afroditi (Frontiers in Public Health, 2023)
Background: The prevention of mobility-related disability among adults is a global healthcare priority. Cost-effective community-based strategies to improve physical function and independence in older adults with mobility limitations are needed. This study investigated the effectiveness of the REtirement in ACTion (REACT) exercise intervention on individual markers of physical function at 6-and 12-months. Methods: The REACT multicentre randomised controlled trial assigned 777 older adults (female, 514; male 263) mean age 77·6 [SD 6·8] years) with reduced lower limb physical functioning (Short Physical Performance Battery [SPPB] score 4-9) to receive brief healthy ageing advice or a 12-month, group-based, multimodal exercise programme delivered in local communities. Estimated differences in the three individual component scores of the SPPB (strength, balance, gait speed) and physical functional outcomes recorded at 6- and 12-months were assessed. Results: The intervention group demonstrated significant improvements in strength (OR=1.88, 95% CI=1.36-2.59, p<0.001) and balance (OR=1.96, 95% CI=1.39-2.67, p<0.001) at 12-months, but not in gait speed (OR=1.32, 95% CI=0.91-1.90, p=0.139). In comparison to the control group, at six-and 12-months, the intervention group reported statistically significant improvements in Mobility Assessment Tool-Short Form (MAT-SF), physical component score from SF-36 questionnaire, and strength and endurance items of subjectively reported physical activity (PASE 10-item). Greater than 75% adherence (attending ≥48 of the 64 exercise sessions delivered in 12-months) was associated with superior functional outcomes. Conclusions: The REACT exercise programme provides local, regional and national service providers with an effective solution to increase muscle strength and balance in older adults at risk of mobility disability.